2018
DOI: 10.1038/s41598-018-30487-6
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β, IL-6, TNF- α and CRP in Elderly Patients with Depression or Alzheimer’s disease: Systematic Review and Meta-Analysis

Abstract: We carried out systematic review and meta-analysis to evaluate whether peripheral levels of pro-inflammatory markers including Interleukin-1 beta (IL-1β), Interleukin-6 (IL-6), Tumor Necrosis Factor-α (TNF- α) and C-Reactive Protein (CRP) are significantly higher in elderly with depression and Alzheimer’s disease. We searched Pubmed, PsycINFO and Embase, and thirty-four relevant studies (2609 with Depression, 1645 with Alzheimer’s disease and 14363 Controls) were included. Compared with controls, IL-1β (pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
243
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 422 publications
(281 citation statements)
references
References 101 publications
(120 reference statements)
7
243
2
3
Order By: Relevance
“…Psychopathology was based on self-report questionnaire data and not clinical interview. Previous research found that depression was associated with raised IL-1β levels [61]; the association between PTSD and IL-1β levels found in this study could be confounded by depression. Further research is required to evaluate the effect of pharmacotherapy to reduce IL-1β levels in refugees as previous research found that antidepressants were able to reduce IL-1β levels [62].…”
Section: Discussioncontrasting
confidence: 55%
“…Psychopathology was based on self-report questionnaire data and not clinical interview. Previous research found that depression was associated with raised IL-1β levels [61]; the association between PTSD and IL-1β levels found in this study could be confounded by depression. Further research is required to evaluate the effect of pharmacotherapy to reduce IL-1β levels in refugees as previous research found that antidepressants were able to reduce IL-1β levels [62].…”
Section: Discussioncontrasting
confidence: 55%
“…COVID-19 can cause acute respiratory syndrome with consequent release of pro-inflammatory cytokines, including interleukin (IL)-1β and IL-6 from the respiratory tract. 22 These cytokines were commonly found to be increased in major depressive disorder 23,24 and functional somatic syndromes 25 . COVID-19, depression and functional somatic syndrome share the same PNI framework.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated whether peripheral IL-6 levels are significantly higher in the elderly with depression. Ng et al carried out a meta-analysis of nine studies to evaluate whether peripheral IL-6 levels are significantly higher in elderly with depression [49]. They found, compared with controls, IL-6 were significantly elevated in the aged depression subjects.…”
Section: Il-6 and Depression Subtypesmentioning
confidence: 99%